To nie „czerwony carat”. Dawna Rosja a Związek Sowiecki w myśli politycznej Józefa Mackiewicza (Politeja, 2022)
NOT THE „RED CZARATE”: OLD-DAY RUSSIA VERSUS THE SOVIET UNION IN THE POLITICAL REFLECTION OF JÓZEF MACKIEWICZThis article discusses Józef Mackiewicz’s views on old Russia and the Soviet Union, attempting to answer the question of whether Mackiewicz saw in totalitarian communist rule a continuation of Russian self-government or a new type of political phenomenon. Unlike most Polish writers and activists of political circles, Mackiewicz does not agree with the thesis formulated by Jan Kucharzewski in his work Od białego tsaratu do czerwonego [From the White to the Red Czarate], that the face of Russia was unchangeable, independent of political changes. Answering the question whether communism was institutionally and mentally rooted in the former Russian statehood, Mackiewicz strongly disagrees. He claims that communism was a completely different phenomenon, transcending systemic differences, which is why calling it “a red czarate” is completely wrong. He consistently separates the concepts of self-government and communism, opposes the view that the Soviet Union was a continuation of tsarist Russia, and therefore rejects the treatment of communist captivity as another iteration of the national dispute between Poland and Russia.